Panniculitis in rheumatology: Unresolved issues - N. M. Savushkina; O. N. Egorova; B. S. Belov (Современная ревматология, 2016)
Panniculitis (PN) is a group of heterogeneous inflammatory diseases characterized by involvement of the subcutaneous fat and frequently locomotor system and viscera. An analysis of the literature suggests that so far there are no studies using a uniform large cohort of patients with different types of PN and further carefully tracking their outcomes over several years. Some authors still question the nosological independence of Weber–Christian PN. The issues of treatment in general and its specific forms remain open. The lack of conventional treatments, regardless of the form of PN, necessitates in vivo clinical trials of various regimens, by compar-ing the course and outcomes of the disease. Recognizing the possible predictors of a relapse in various forms of PN and assessing the long-term results of treatment are of supreme importance since, along with an analysis of the efficiency of different therapy regimens, valuable informa-tion on diverse factors that significantly influence the prognosis of the disease can be obtained.